2022
DOI: 10.3390/ijms231710125
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Shortening and Increased Oxidative Stress in Lumbar Disc Degeneration

Abstract: Lumbar disc degeneration (LDD) contributes to low back pain. This study aimed to determine relative telomere length (RTL), oxidative stress status, and antioxidant levels and examine the relationships between RTL, oxidative stress, and the severity in LDD patients. A total of 100 subjects, 50 LDD patients and 50 healthy controls, were enrolled in the case–control study. Blood leukocyte RTL was analyzed using quantitative real-time polymerase chain reaction. Lipid peroxidation was determined by malondialdehyde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The content of 8‐oxoG in body fluid of patients with oxidative stress‐related psychiatric disorders, chronic kidney disease, gestational diabetes, and neurodegenerative diseases increased 74–77 . In addition, a case–control study found that plasma 8‐oxodG levels in patients with lumbar disc herniation were significantly higher than those in healthy controls 78 . Recently, it was found that the level of 8‐oxodG in human NPCs induced by IL‐1β is significantly increased, while the level of 8‐oxodG is decreased after treatment with antioxidants 79 .…”
Section: Oxidative Damage Of Biomoleculesmentioning
confidence: 99%
See 3 more Smart Citations
“…The content of 8‐oxoG in body fluid of patients with oxidative stress‐related psychiatric disorders, chronic kidney disease, gestational diabetes, and neurodegenerative diseases increased 74–77 . In addition, a case–control study found that plasma 8‐oxodG levels in patients with lumbar disc herniation were significantly higher than those in healthy controls 78 . Recently, it was found that the level of 8‐oxodG in human NPCs induced by IL‐1β is significantly increased, while the level of 8‐oxodG is decreased after treatment with antioxidants 79 .…”
Section: Oxidative Damage Of Biomoleculesmentioning
confidence: 99%
“…87 In a recent study, plasma levels of malondialdehyde (MDA), a lipid peroxidation product, were significantly higher in patients with lumbar disc herniation compared with healthy controls. 78 In addition, tertbutyl hydroperoxide (TBHP) and H 2 O 2 could also increase the MDA level in rat IVD cells. [88][89][90] These studies all suggest that oxidative stress can lead to lipid peroxidation within IVD, which in turn promotes IDD progression.…”
Section: Oxidative Damage Of Lipidmentioning
confidence: 99%
See 2 more Smart Citations
“…Lumbar disc degeneration (LDD) is one of the fundamental causes of low back pain. Clinically, symptoms of LDD are low back pain, difficulty walking, and impaired musculoskeletal muscle, leading to severe pain and decreased quality of life [ 2 , 3 ]. Several multifactorial factors contributing to the pathogenesis of LDD include mechanical stress, obesity, aging, previous injury, and genetic factors.…”
Section: Introductionmentioning
confidence: 99%